Hospitality and anti-tourist attitudes through the host-guest relationship in the Westworld science fiction series - Ramón Cardona, José; Sánchez Fernández, María Dolores; Soares, Jakson Renner Rodrigues (Turyzm/Tourism, 2024)
Westworld is a science fiction series that proposes a theme park of the future where ‘guests’ can live a Wild West experience without restrictions or reprisals, thanks to reallooking android ‘hosts’ who grant all their wishes. Due to the topic covered, this science fiction series allows its use as a common thread for an article that considers the concept of hospitality, the host-guest relationship and its consequence for the management of tourist destinations. This is achieved through an exegesis of Westworld and an analysis of academic bibliography. First, different concepts of hospitality and what they imply for the host-guest relationship are identified. Subsequently, how different theoretical developments on the resident-tourist relationship are proposed entailing different interpretations and reactions to the same objective reality. In conclusion, it should be noted that when tourism is perceived as subordinating the host to the wishes of the guest (as in Westworld), the appearance of anti-tourism attitudes among residents is only a matter of time, generating conflicts. Furthermore, the importance of dominant interpretive theories in determining the reaction of the local population to events that occur should be highlighted.